Millennials imbabureños y sus preferencias de uso de redes sociales durante la pandemia Covid-19 en el 2020 - Valenzuela Arroyo, David (Revista Ecos de la Academia, 2023)
The Covid-19 pandemic highlighted the use of social networks by the entire population, in Imbabura the so-called millennial generation is the most economically active group and precisely from there the objective of the present investigation arises: to determine the preferences of use of the social networks of generation Y, establishing the categories of little, moderate and a lot of use of the main networks such as Facebook, YouTube, Instagram, WhatsApp, Tik Tok, Vimeo, Twitter among others. This is an investigation framed in the non-experimental quantitative approach with a correlational scope with a cross section; The sample studied was 1,408 people between the ages of 20 and 40 at the date of the study, residents of the province of Imbabura. A survey was applied to this group and the data obtained was analyzed using quantitative methods for analysis of type scales. Likert, which results in a moderate use of social networks in most respondents. Using the cross tables, the behavior of gender with respect to the categories of use was evidenced and using the Chi Square hypothesis test, it was found that there is a relationship between the use of social networks with the gender of the person. Using the first quartile of the category of heavy use of social networks, it is concluded that the millennial generation group of Imbabura uses only certain types of networks very frequently.